EXPERIENCE IN INTEGRATION OF MASS OPEN ONLINE COURSES INTO FORMAL EDUCATION - Dehtiarova, Nelia; Petrenko, Lyudmyla; Zhmud, Oksana; Makarova, Victoria (Physical and Mathematical Education, 2024)
Formulation of the problem. The mismatch between the content of education and modern requirements for learners, constant reduction of hours in formal education, occasionally outdated material, loss of popularity and authority of formal education institutions are the contradictions that make non-formal education relevant. Massive Open Online Courses (MOOCs) are emerging as a promising solution, offering the opportunity to quickly acquire necessary knowledge and skills, choose various courses on different platforms, select tutors, and control the pace of learning. This study focused specifically on the features of integrating non-formal education into formal education, to theoretically substantiate and experimentally test the effectiveness of MOOCs in bridging the gap between formal education and the evolving needs of future computer science teachers.Materials and Methods. To address the research problem, we used theoretical methods: analysis of scientific sources on the state of the research problem, generalization of personal experience, study of methodological materials, and normative sources. Experimental research was also conducted, including surveys, pedagogical experiments, statistical processing of results, and investigation of experiment participants' reflective perception of results.Results. This work continues the research that began in 2021; some results have been published previously. The research started with a survey. The paper presents some results from 2023 and analyzes changes compared to a similar study of respondents in 2021-early 2022. The next step was an initial diagnosis - a control test of knowledge in the disciplines of "Digital Technologies," "Information and Communication Technologies," and "Computer Science" (depending on the educational program). The results showed that an increase in the number of students in the experimental group who achieved high and sufficient levels and a decrease in their number at the average and low levels indicate the effectiveness of integrating non-formal education into formal education. These changes were more evident in the experimental group.Conclusions. Over 2 years, attitudes towards massive open online courses (MOOCs) have significantly shifted: the number of respondents fully engaging in informal education has increased; the number of respondents using Ukrainian platforms EdEra, Prometheus, and Diya has also grown; and the issue of access to courses in cities and towns where there is no warfare is not significant. This positive change in attitudes and usage patterns indicates a growing acceptance and effectiveness of MOOCs in formal education. Recommendations for the integration of MOOCs into formal education were summarized. We see promising prospects for further research in developing courses and placing them on specific platforms to support formal education in Secondary Education (Computer Science).
Keywords: non-formal education; Massive Open Online Courses; MOOCs; computer in education; self-education; lifelong learning; challenging learning conditions